(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Romantics: A Novel, depicts the protagonist Samar, a Brahmin boy more or less rooted in the Indian traditional mind set but at the same time drifted away to a great extent by the type of education prevailing in India. His western education tends him to be in the company of some characters from the West who are on a sojourn in India. The confrontation ends up in disillusionment and dejection. A probe into the reasons bring out the nuances of the divide between the Orient and the Occident.